Dampak Limbah Makanan di Sektor Rumah Tangga terhadap Keberlangsungan Lingkungan - Alliffiya Alkhansyah Arsy; Ferdi Irwansyah; Laurena Ginting; Vina Gabriela Saragih (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
Food waste generated from the household sector is one of the largest contributors to environmental degradation in Indonesia. Food waste generated from the household sector is one of the main contributors to the increasing volume of organic waste in Indonesia. This issue not only creates social and economic problems but also poses a serious threat to environmental sustainability. This study aims to analyze the contribution of household food waste to environmental degradation and to review sustainable management strategies. This study employs a Systematic Literature Review (SLR) method guided by the PRISMA 2020 Statement to review relevant national research conducted during the period 2018-2025. The results of the literature selection show that the impacts of household food waste on environmental sustainability can be categorized into three main dimensions: (1) ecological impacts, including pollution and the increase of greenhouse gas emissions; (2) resource impacts, such as the wastage of energy, water, and land; and (3) social-environmental impacts, including the increasing burden of regional waste management and the declining quality of life for communities living near landfills. The findings emphasize that the management of household food waste plays a crucial role in achieving environmental sustainability, particularly in supporting the attainment of Sustainable Development Goal (SDG) 12, which focuses on responsible consumption and production. Therefore, it is necessary to implement strategies of reduction, reuse, and recycling of food waste at the household level to minimize the negative impacts on environmental sustainability in Indonesia.